Expression of mammalian mitochondrial F1‐ATPase in Escherichia coli depends on two chaperone factors, AF1 and AF2. Issue 12 (25th October 2016) - Suzuki, Toshiharu; Iida, Naoya; Suzuki, Junko; Watanabe, Yasunori; Endo, Toshiya; Hisabori, Toru; Yoshida, Masasuke
Abstract : F1 ‐ATPase (F1 ) is a multisubunit water‐soluble domain of Fo F1‐ ATP synthase and is a rotary enzyme by itself. Earlier genetic studies using yeast suggested that two factors, Atp11p and Atp12p, contribute to F1 assembly. Here, we show that their mammalian counterparts, AF1 and AF2, are essential and sufficient for efficient production of recombinant bovine mitochondrial F1 in Escherichia coli cells. Intactness of the function and conformation of the E. coli ‐expressed bovine F1 was verified by rotation analysis and crystallization. This expression system opens a way for the previously unattempted mutation study of mammalian mitochondrial F1 . Abstract : Bovine mitochondrial F1 ‐ATPase was successfully expressed in Escherichia coli cells with the assistance of two bovine chaperone factors, AF1 and AF2. Intactness of the function and conformation of the recombinant bovine F1 was verified by single‐molecule analysis of the ATPase‐driven rotation and by crystallization. This is the first demonstration of rotation of bovine F1 ‐ATPase.